Autokorelasi Spasial Prevalensi Ketidakcukupan Konsumsi Pangan di Pulau Kalimantan Tahun 2024 - Baharuddin (PT. Lontara Digitech Indonesia, 2025)
Food security remains a serious challenge in Indonesia, marked by high disparities among regencies/ cities, including in Kalimantan Island. This study aims to identify disparities and spatial patterns in the prevalence of food consumption inadequacy in Kalimantan Island in 2024, test for spatial autocorrelation, and identify regional clusters based on prevalence characteristics. The methods used were exploratory and inferential spatial analysis, including the measurement of global spatial autocorrelation using Moran's I and the identification of local clusters using LISA (Local Indicators of Spatial Association). The results reveal significant positive spatial autocorrelation (global Moran's I = 0.64), with “High-High” clusters concentrated in West Kalimantan and North Kalimantan, and “Low-Low” clusters in South Kalimantan. These findings imply the necessity for cluster-based and context-specific policy approaches to effectively enhance food security.